2016
DOI: 10.1007/s11605-015-3049-z
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Treatment of Abdominal Arterial Bleeding After Radical Gastrectomy: a Retrospective Analysis of 1875 Consecutive Resections for Gastric Cancer

Abstract: BackgroundMassive abdominal arterial bleeding is an uncommon yet life-threatening complication of radical gastrectomy. The exact incidence and standardized management of this lethal morbidity are not known.MethodsBetween January 2003 and December 2013, data from 1875 patients undergoing radical gastrectomy with D2 or D2 plus lymphadenectomy were recorded in a prospectively designed database from a single institute. The clinical data and management of both early (within 24 h) and late (beyond 24 h) postoperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 33 publications
3
35
0
4
Order By: Relevance
“…The overall postoperative arterial hemorrhage rate was 1.92%, with a relatively high mortality rate of 33.3%. It is mostly caused by abdominal arterial bleeding, mainly from branches of the celiac trunk, the common hepatic artery and its branches and splenic artery (31). Rupture of abdominal arteries can provoke not only massive abdominal bleeding but also intraluminal bleeding.…”
Section: Hemorrhagementioning
confidence: 99%
“…The overall postoperative arterial hemorrhage rate was 1.92%, with a relatively high mortality rate of 33.3%. It is mostly caused by abdominal arterial bleeding, mainly from branches of the celiac trunk, the common hepatic artery and its branches and splenic artery (31). Rupture of abdominal arteries can provoke not only massive abdominal bleeding but also intraluminal bleeding.…”
Section: Hemorrhagementioning
confidence: 99%
“…Recent research suggetsed that TAE is a safe treatment method for gastrointestinal bleeding. Authors have reported satisfactory results of TAE compared to surgery for treatment of bleeding after gastric cancer resection, duodenal bleeding, severe bleeding of upper gastrointestinal tumors and bleeding gastroduodenal ulcers [6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…1). 6,7 The hemorrhage may be caused by a weakened arterial wall due to arterial skeletonization (dissection of the arterial fibrous sheath or adventitial layer) after aggressive lymphadenectomy. 8 Abdominal abscess, which will be discussed later in this article, can be a cause of bleeding at period several days after surgery by erosion of adjacent vessels.…”
Section: Etiologymentioning
confidence: 99%
“…3,7 In the late postoperative period, however, angiography and transarterial embolization (TAE) should be considered as first-line treatment, since the bleeding site is difficult to find surgically due to adhesions, inflammatory reactions, and friability of postoperative tissues. 6,7 Furthermore, TAE is a less invasive approach, irrespective of tissue adhesions and friability caused by primary surgery.…”
Section: Treatmentmentioning
confidence: 99%